On the total curvature of curves in nonsymmetric Minkowski spaces - Borisenko, A.A.; Miroshnichenko, S.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The estimations of the total curvature of closed curves in nonsymmetric Minkowski spaces are obtained. Generalizations of the Fenchel and Fary–Milnor theorems are proved. The evaluation of the lengths of closed curves in a ball with fixed radius in the Minkowski space is presented.